K.H. Ahmad Dahlan Sebagai Tokoh Pembaharu - M, M Dahlan (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
Ahmad Dahlan is one of the reformer figure in Moslem of Indonesia who we couldnât deny him. Ahmad Dahlanâs movement was very incredible to redesign the consciousness of reformer in our societies which we could felt it now. Ahmad Dahlan in his revolution movement had planned to made direction of Meccaâs to be corrected, to fixed Bidâah and Khurafat, his development in social side and education in an organization had called Muhammadiyah. Muhammadiyah had given so much incredible benefits to development of Indonesia societies, especially the Moslem of Indonesia.